Microplastics effects in Scrobicularia plana - Ribeiro, Francisca (2018)
One of the most common plastics in the marine environment is polystyrene (PS) that can be broken down to micro sized particles. Marine organisms are vulnerable to the exposure to microplastics. This study assesses the effects of PS microplastics in tissues of the clam Scrobicularia plana. Clams were exposed to 1mgL-1(20μm) for 14days, followed by 7days of depuration. A qualitative analysis by infrared spectroscopy in diffuse reflectance mode period detected the presence of microplastics in clam tissues upon exposure, which were not eliminated after depuration. The effects of microplastics were assessed by a battery of biomarkers and results revealed that microplastics induce effects on antioxidant capacity, DNA damage, neurotoxicity and oxidative damage. S. plana is a significant target to assess the environmental risk of PS microplastics.